A Comparison of Media Competency in Political Communication on Twitter among Presidential Candidates during their Election Campaigns in Spain, Ecuador and Colombia - Conde, Manuel Antonio (2019)
A comparison of media competency in political communication on Twitter among presidential candidates during election campaigns in Spain, Ecuador and Colombia. Currently, political communication is usual on social networks, especially on Twitter. This research has highlighted the media competencies of 12 presidential candidates in Spain, Ecuador and Colombia. To that end, the four main leaders of each country were chosen. Using Twitter’s advanced search tool, data mining yielded a total of 3,707 tweets sent by these candidates during their election campaigns, out of which 590 had an audiovisual element, 1,743 had photographs and 1,174 used hashtags. A quantitative research was chosen due to its significance for data analysis with a flexible and exploratory method, since this subject has not been studied in depth before